A review of teachers’ assessment literacy proficiency measures - Geng Juanjuan; Nurahimah Mohd Yusoff (International Journal of Evaluation and Research in Education (IJERE), 2022)
At present, there are several literature reviews on teachers’ assessment literacy (AL). However, little attention has been paid to a systematic analysis of AL measures. The review on AL measures helps to evaluate the available tools and provide recommendations for developing AL measures in further exploration. Hence, the purpose of the current literature review is to focus on analyzing the measures of teachers’ AL proficiency from 1991 to 2020. Across the contexts, 28 quantitative tools made up of questionnaires or tests were collected. Among them, 10 were designed to investigate overall AL proficiency and 18 were constructed to examine the sub-categories of AL proficiency among teachers. Each instrument was analyzed from the format, guiding framework, item characteristics, targeting population, and psychometric quality. Results showed that the current AL measures were derived more from instrumental than social-cultural conceptualization, examined more on sub-categories than the overall proficiency level, targeted more at in-service teachers than pre-service teachers, and focused more on elementary and middle education than pre- or higher education. Further studies are welcomed from four aspects: construct social-culturally, test generalizability, target at specific groups, and cover various types of AL.